Cities in Contemporary Africa
XIV, 318 p. 16 illus.
Keywords: This book explains how and why cities on the African continent have grown at such a rapid pace, how municipal authorities have tried to cope with this massive influx of people, and how long-time urban residents and newcomers interact, negotiate, and struggle over access to limited resources.